Intercultural Miscommunications Faced by UTM Students and the Strategies They Use to Overcome Them - Alkelani, Waseem (Eximia, 2023)
The phenomenon of intercultural communication is increasing day by day due to the new trend of global economy which brings people from various ethnicities and nationalities to work together in the same places. There is a need to look into this type of communication and have a closer look at the possible causes of miscommunication. This paper looks into intercultural miscommunication between international and local students in one of the major multicultural universities in Malaysia. It examines the quality of intercultural communication through investigating the various challenges students face in this regard as well as the different strategies they use to avoid and fix miscommunication. Interviews were conducted on 20 students. It was found that the participants of the study face various challenges which were classified into linguistic and cultural ones. The present paper invites researchers to further examine the various challenges that face both groups of students in this regard.